2022
DOI: 10.3389/fpls.2022.922581
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Metabolic Responses of Maize Shoots to Long-Term Potassium Deficiency

Abstract: Potassium is important for plant growth and crop yield. However, the effects of potassium (K+) deficiency on silage maize biomass yield and how maize shoot feedback mechanisms of K+ deficiency regulate whole plant growth remains largely unknown. Here, the study aims to explore the maize growth, transcriptional and metabolic responses of shoots to long-term potassium deficiency. Under the K+ insufficiency condition, the biomass yield of silage maize decreased. The transcriptome data showed that there were 922 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
6
2
Order By: Relevance
“…This study revealed that the content of Phe in the FBR-treated group fruit increased 2.33-fold compared with that in the FPR (CK) group, which may promote the synthesis of polyphenols in the FBR treatment group. Additionally, the highest K content in the FBR substrate may also play an important role in the metabolism of amino acids in the fruit, since K is closely related to the biosynthesis, transformation, and distribution of metabolites [ 56 , 57 ]. Sugar is an indispensable part of the plant growth process; it not only provides a carbon skeleton for plants, but also increases the resistance of plants [ 10 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the content of Phe in the FBR-treated group fruit increased 2.33-fold compared with that in the FPR (CK) group, which may promote the synthesis of polyphenols in the FBR treatment group. Additionally, the highest K content in the FBR substrate may also play an important role in the metabolism of amino acids in the fruit, since K is closely related to the biosynthesis, transformation, and distribution of metabolites [ 56 , 57 ]. Sugar is an indispensable part of the plant growth process; it not only provides a carbon skeleton for plants, but also increases the resistance of plants [ 10 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes related to organic and amino acid metabolism was significantly altered in oats under P deficiency ( Wang et al., 2018 ). In maize seedlings under K + deficiency stress, MAPK signaling pathway-plant, signal transduction mechanisms, plant hormone signal transduction, and amino acid transport and metabolism were the mainy enriched pathways, and related gene expression was significantly altered ( Xiong et al., 2022 ) In our study, in coconut seedling leaves under K + deficiency stress, “MAPK signaling pathway-plant”, “signal transduction mechanisms”, “plant hormone signal transduction”, “amino acid transport and metabolism”, “plant-pathogen interaction”, “starch and sucrose metabolism”, “spliceosome”, “endocytosis”, “ABC transporters”, “fatty acid elongation”, and “protein kinase/protein domain” pathways were affected. In particular, genes related to “MAPK signaling pathway-plant”, “signal transduction mechanisms”, “plant hormone signal transduction”, “amino acid transport and metabolism” pathways were significantly down-regulated ( Supplementary Tables 7, 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In different substances, whether up-or down-regulated, each metabolite, whether up- or down-regulated, plays a different role and plays a very important role in response to low-K + stress. For example, sugars such as raffinose, radish sugar, and glucosamine are accumulated in low-K + stress, and are also detected in plants under P or cold stress ( Cook et al., 2004 ; Ding et al., 2021 ; Xiong et al., 2022 ). Flavonoids and phenols are major secondary metabolites involved in plant immunity ( Wang and Wu, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations